2009
DOI: 10.1136/ard.2008.105254
|View full text |Cite
|
Sign up to set email alerts
|

Role of European mitochondrial DNA haplogroups in the prevalence of hip osteoarthritis in Galicia, Northern Spain

Abstract: The results of this study support the hypothesis that the mtDNA haplogroups have a role in the complex osteoarthritic process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(64 citation statements)
references
References 15 publications
1
62
0
1
Order By: Relevance
“…The mechanisms by which stimulation of Fas by the Fas ligand initiates apoptosis have been extensively investigated, and it has been demonstrated that cell death in primary OA chondrocytes is mediated by the Fas pathway [90]. mtDNA variation has been associated with risk of OA of the knee [91] and of the hip [92]. Given the role of mtDNA damage in mitochondria-driven apoptosis, it is possible to speculate that the involvement of mtDNA haplotypes in OA risk may relate to apoptotic pathways.…”
Section: Molecular Pathogenesis and Genetics Of Osteoarthritis Reviewmentioning
confidence: 99%
“…The mechanisms by which stimulation of Fas by the Fas ligand initiates apoptosis have been extensively investigated, and it has been demonstrated that cell death in primary OA chondrocytes is mediated by the Fas pathway [90]. mtDNA variation has been associated with risk of OA of the knee [91] and of the hip [92]. Given the role of mtDNA damage in mitochondria-driven apoptosis, it is possible to speculate that the involvement of mtDNA haplotypes in OA risk may relate to apoptotic pathways.…”
Section: Molecular Pathogenesis and Genetics Of Osteoarthritis Reviewmentioning
confidence: 99%
“…Conversely, smoking has also been related with a higher prevalence of knee pain [6] and knee cartilage loss [7,8]. In this area, a retrospective multivariate analysis performed by our group on hip OA samples revealed a negative association between smoking and OA [9].…”
Section: Clinical Relevancementioning
confidence: 96%
“…Il existe probablement une mort cellulaire accrue des chondrocytes au cours de l'arthrose qui pourrait impliquer l'ADN mitochochondrial (ADNmt) dont certaines séquences seraient associées à l'arthrose de hanche et de genou [32,33]. Plus récem-ment, un effet protecteur du polymorphisme rs7164503 du gène ANP32A suppresseur de tumeur a été observé sur le risque de coxarthrose et dans une moindre mesure de gonarthrose dans une étude regroupant quatre cohortes, soit 2170 individus arthrosiques et 2849 témoins féminins [24].…”
Section: Apoptose Et Mort Cellulaireunclassified